Respuesta :

gmany

[tex]a)\\\dfrac{2}{3}\div\dfrac{1}{4}=\dfrac{2}{3}\cdot\dfrac{4}{1}=\dfrac{8}{3}=2\dfrac{2}{3}\\\\b)\\\dfrac{7}{5}\cdot8=\dfrac{56}{5}=11\dfrac{1}{5}\\\\c)\\\dfrac{2}{5}-\dfrac{1}{3}\\\text{common denominator is (5)(3) = 15}\\\\\dfrac{2\cdot3}{5\cdot3}-\dfrac{1\cdot5}{3\cdot5}=\dfrac{6}{15}-\dfrac{5}{15}=\dfrac{1}{15}\\\\d)\\\dfrac{3}{10}+2\dfrac{7}{12}\\\text{common denominator is 60}\\\\\dfrac{3\cdot6}{10\cdot6}+2\dfrac{7\cdot5}{12\cdot5}=\dfrac{18}{60}+2\dfrac{35}{60}=2\dfrac{53}{60}[/tex]

ACCESS MORE